Role of Librarians in the New Millennium of Information Technology - Murthy, S.S. (DESIDOC Journal of Library & Information Technology, 2003)
This article highlights the librarians' connotations of information Technology (IT), IT developments in libraries, and areas of IT as relevant to libraries. It also discusses the future IT use and role of librarians in future. http://dx.doi.org/10.14429/dbit.19.4.3492